A developmental and negotiated approach to school self-evaluation - Lai, Mei Kuin.; Kushner, Saville (Bingley, U.K. : Emerald, 2013)
Current conventions in school evaluation focus on accountability, control and compliance. New Zealand offers a distinctive, systemic alternative to school self-evaluation, with developmental and negotiated approaches ingrained throughout the education system, from school inspection to major government schooling improvement initiatives. In New Zealand there is no national testing, other than a Ministry-sponsored (voluntary) formative assessment system designed for school and teacher self-evaluation. This is a form of professional and program evaluation where there is shared power and responsibility between evaluators and those being evaluated. Through a detailed national case study of New Zealand, together with commentaries from international specialists, this volume examines the successes and challenges of this approach to programme evaluation and its generalizability to other educational and professional review settings, and show how education systems can recover a balance between an achievement agenda and a focus on educational quality.
Preface : walking backwards into the future / Mei Lai, Saville Kushner -- Enhancing the quality of education through school self-evaluation / Helen Simons -- Introduction to the New Zealand case / Mei Lai, Saville Kushner -- The New Zealand educational context : evaluation and self-review in a self-managing system / Helen S. Timperley -- AsTTle : a national testing system for formative assessment : how the national testing policy ended up helping schools and teachers / Gavin T.L. Brown -- A thousand flowers blooming : the implications of school self-review for policy developers / Mei Lai -- Evaluation in effective research-practice partnerships / Stuart McNaughton ... [et al.] -- Introduction to the education review office chapters / Saville Kushner -- Developing a conceptual framework for school review / Carol Mutch -- Changing the professional culture of school review : the inside story of ERO / Steffan Brough, Steve Tracey -- Evaluation as a double-edged sword : building schools evaluative capability while evaluating their efforts in raising achievement / Judy M. Parr, Helen S. Timperley -- Leaders' use of classroom evidence to understand, evaluate and reform schooling for indigenous students / Mere Berryman -- School improvement through theory engagement / Viviane M.J. Robinson, Helen S. Timperley -- Looking forward : evaluation in New Zealand education / Lorna M. Earl -- New Zealand style school review : a view from outside / Katherine E. Ryan, Jennifer Timmer -- An introduction to international contrasts / Mei Lai, Saville Kushner -- School self-evaluation in the longer time scale. Experiences from a small Scandinavian state / Ola Johan Sjøbakken, Stephen Dobson -- Data-centered school self-evaluation in the Netherlands : characteristics and prerequisites / Kim Schildkamp, Adrie Visscher -- Exploring the possibilities and methodological challenges of evaluation practice : a democratic question / Val Klenowski, Annette Woods -- Judging and explaining the quality of school self-evaluations : indicators and findings on meta-evaluation from a Flemish perspective / Jan Vanhoof, Peter Van Petegem.
Includes index.
Print version record
Keywords: Education -- Curricula; Education -- Testing & Measurement; Education -- Educational Policy & Reform -- General; Organization & management of education; Examinations & assessment; Educational evaluation